2014
DOI: 10.1186/s12870-014-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct double flower varieties in Camellia japonica exhibit both expansion and contraction of C-class gene expression

Abstract: BackgroundDouble flower domestication is of great value in ornamental plants and presents an excellent system to study the mechanism of morphological alterations by human selection. The classic ABC model provides a genetic framework underlying the control of floral organ identity and organogenesis from which key regulators have been identified and evaluated in many plant species. Recent molecular studies have underscored the importance of C-class homeotic genes, whose functional attenuation contributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…Previous studies in Camellia characterized the expression of A-, and C- function genes and suggested that double flower domestication were involved in multiple pathways 27 . Interestingly, the expression of C function ortholog ( CjAG ) displayed opposite patterns in petals of formal and anemone doubles (expression of CjAG suppressed in formal double, but upregulated in anemone double) 27 . Despite the extensive knowledge on genetic regulation of floral development in the model plant species, it remains unclear how the floral patterns in cultivated Camellia were achieved.
Figure 1Comparative transcriptomics analysis in wild and doubled camellias.
…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Camellia characterized the expression of A-, and C- function genes and suggested that double flower domestication were involved in multiple pathways 27 . Interestingly, the expression of C function ortholog ( CjAG ) displayed opposite patterns in petals of formal and anemone doubles (expression of CjAG suppressed in formal double, but upregulated in anemone double) 27 . Despite the extensive knowledge on genetic regulation of floral development in the model plant species, it remains unclear how the floral patterns in cultivated Camellia were achieved.
Figure 1Comparative transcriptomics analysis in wild and doubled camellias.
…”
Section: Introductionmentioning
confidence: 99%
“…For example, in filled flowers, stamens and carpels are replaced by sepals and petals; according to the ABC model, C-class gene expression is expected to be affected in the innermost whorls. Such a hypothesis has been confirmed in filled flowers of Camellia japonica (Sun et al, 2014) and Ipomoea nil (Nitasaka, 2003). Similarly, double flowers with an increased number of petals and/or petaloid stamens and a decrease in stamen number, may correspond to mutation(s) shifting the expression domain of C-class genes.…”
Section: Moquin-tandonmentioning
confidence: 82%
“…Similarly, double flowers with an increased number of petals and/or petaloid stamens and a decrease in stamen number, may correspond to mutation(s) shifting the expression domain of C-class genes. Such a shift in the expression domain of AG homologues has been described in species with double flowers belonging to Rosa sp, Prunus lannesiana, Camellia japonica and Lilium (Dubois et al, 2010;Liu et al, 2013;Sun et al, 2014;Akita et al, 2008Akita et al, , 2011. In the Orchidaceae family, the characterization of genes from the extended ABCE model, with a focus on the B-class genes has given clues about the genetic origin of peloric flowers in some species.…”
Section: Moquin-tandonmentioning
confidence: 97%
“…Thus, attenuated Cclass function could increase petal development, inhibit stamen development, and also increase the floral organ number, which is consistent with the formation of double flowers. Double-flowered phenotypes result from C-function repression in a number of horticultural plants, including Gentiana scabra (Nakatsuka et al, 2015), Camellia japonica (Sun et al, 2014), Petunia hybrida (Noor et al, 2014), and Cyclamen persicum (Tanaka et al, 2013). Therefore, it is likely that the double flowers of Japanese azalea cultivars result from lost or impaired C-function genes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to transgenic flowers, the double-flowered cultivar 'Shibaxueshi' (Camellia japonica) is a typical formal double type with petals from the outer layer to the inside. Furthermore, the stamens and carpels were missing and the expression levels of CjAG in floral buds were markedly reduced, suggesting that the loss of CjAG expression is involved in double flower development (Sun et al, 2014). In Cyclamen double-flowered cultivars, the lack of CpAG1 expression causes the homeotic conversion of stamens and carpels into petals (Tanaka et al, 2013).…”
mentioning
confidence: 99%